LEGAL EXPLANATION ABOUT PREMANISM AND ENFORCEMENT OF THEIR LAW IN SUNGAI LUAR VILLAGE, BATANG TUAKA DISTRICT, INDRAGIRI HILIR REGENCY - Fitri Wahyuni; Siti Rahmah; Darmiwati Darmiwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2021)
Thuggery is a crime that very often occurs not only in cities but also in rural areas. It is not uncommon for this crime to cause victims so that the community feels uneasy about the crime. one of them is a village that is a place of thuggery is a river village outside Batang Tuaka sub-district. The law study program at the law faculty of the Islamic University of Indragiri conducted legal counseling about the dangers of thuggery in the village as a preventive measure so that the crime of thuggery does not happen again. with Data Collection Techniques in the form of Library Studies and Lectures, data sources are through Primary Law materials, namely positive legal materials that are binding and consist of statutory regulations and Secondary Law materials. Qualitative descriptive analysis method. The results of the legal counseling show that thuggery crimes are increasingly occurring due to the lack of public knowledge about the legal rules that thuggery can be subject to criminal sanctions as regulated in the Criminal Code. So far, the community considers that thuggery crimes cannot be sanctioned because people are afraid to report them because thugs always threaten the victim and his family